2016
DOI: 10.1080/01635581.2016.1250921
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Prognostic Nutritional Index for All Stages of Pancreatic Cancer

Abstract: Nutritional status affects the prognosis of various tumors. The prognostic nutritional index (PNI) is the known predictor of postoperative outcome in resectable pancreatic cancer patients. This study aimed to validate the prognostic value of PNI in all stages of pancreatic cancer. We retrospectively reviewed 499 patients with pancreatic cancer who were diagnosed at Severance Hospital between January 2006 and December 2011. The PNI value was calculated as 10 × serum albumin (g/dL) + 0.005 × total lymphocyte cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
0
52
0
1
Order By: Relevance
“…[8][9][10][11] The prognostic nutritional index (PNI), a combination of the serum albumin (Alb) concentration and total lymphocyte count (TLC) in peripheral blood, has been repeatedly shown to reliably reflect the magnitude of the systemic inflammation and the immunonutritional status of patients with many tumor types, including the pancreatic-, colorectal, gastric-, hepatocellular-, and lung cancers, malignant pleural mesothelioma, and glioblastoma multiforme. [12][13][14][15][16][17][18] However, to date, very few studies have been reported to assess the prognostic and/or predictive value of PNI in patients with LA-NPC. [19][20][21][22][23] In these studies, variable cutoffs those determined with various methodologies were utilized for discrimination of the outcomes usually with an end goal of 1 or 2 survival results.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The prognostic nutritional index (PNI), a combination of the serum albumin (Alb) concentration and total lymphocyte count (TLC) in peripheral blood, has been repeatedly shown to reliably reflect the magnitude of the systemic inflammation and the immunonutritional status of patients with many tumor types, including the pancreatic-, colorectal, gastric-, hepatocellular-, and lung cancers, malignant pleural mesothelioma, and glioblastoma multiforme. [12][13][14][15][16][17][18] However, to date, very few studies have been reported to assess the prognostic and/or predictive value of PNI in patients with LA-NPC. [19][20][21][22][23] In these studies, variable cutoffs those determined with various methodologies were utilized for discrimination of the outcomes usually with an end goal of 1 or 2 survival results.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their independent associations with survival in these patients, it is reasonable to combine information on serum albumin and ALC into a composite index abbreviated PNI as previously proposed by Onodera et al [16]. PNI is considered to reflect inflammatory, nutritional and immune status of an oncological patient and was shown to be of prognostic value in a variety of malignant neoplastic diseases [17][18][19][20][21][22]. As we have observed in our cohort of myelofibrosis patients, a quarter of patients presenting with the lowest PNI values (<47) had lower WBC count, lower hemoglobin level, lower serum iron level and lower transferrin saturation in addition to lower serum albumin concentration and lower ALC which all might have been affected by the nutritional status of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…The Prognostic Nutritional Index (PNI), as proposed by Onodera et al [16], integrates information on these two parameters and is calculated as PNI = serum albumin (g/L) + [5 × ALC (×10 9 /L)]. This simple indirect measure of immunocompetence, inflammatory and nutritional status has been shown to be predictive of overall survival and perioperative complications in various malignancies [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…During vaccination, five of the 6 eligible PDA patients had a low PNI (≤49.5), which is a risk factor for a poor prognosis, especially in patients with resectable and metastatic disease. 34 Although 5 of the 6 eligible PDA patients had a low PNI, the administration of 3 to 4 types of therapy in combination resulted in a prolonged OS. One PDA patient with a high PNI (=51.9) during vaccination remained alive for more than 2747 days.…”
Section: Discussionmentioning
confidence: 99%